2021
DOI: 10.3390/ijerph18189864
|View full text |Cite
|
Sign up to set email alerts
|

Association between Statins and Retinal Vascular Occlusion: A Population-Based Cohort Study

Abstract: Retinal vascular occlusion (RVO), including retinal arterial occlusion and retinal vein occlusion, is a common retinal vascular disease that causes visual disturbance. The exact pathogenesis of RVO remains unclear. In all types of RVO patients, hyperlipidemia is more than twofold more common than in controls. Statins have been used to control blood cholesterol levels and have been found to reduce the risk of cardiovascular morbidity and mortality. Moreover, the immunomodulatory functions of statins may play a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
1
2
0
2
Order By: Relevance
“…Retinal arterial occlusion has been previously reported after vaccination with the mRNA COVID-19 vaccine, and were characterized by non-embolic, not accompanied by carotid plague or stenosis, rapid development within 2 weeks after vaccination, and without marked abnormalities of laboratory tests (such as increased D-dimer and C-reactive protein) [7]. The mean age of patients diagnosed with retinal vascular occlusion in the present study was 53 years, which was comparable to that of patients diagnosed with retinal vascular occlusion not associated with vaccination (53 years old) [25].…”
Section: Discussionsupporting
confidence: 53%
“…Retinal arterial occlusion has been previously reported after vaccination with the mRNA COVID-19 vaccine, and were characterized by non-embolic, not accompanied by carotid plague or stenosis, rapid development within 2 weeks after vaccination, and without marked abnormalities of laboratory tests (such as increased D-dimer and C-reactive protein) [7]. The mean age of patients diagnosed with retinal vascular occlusion in the present study was 53 years, which was comparable to that of patients diagnosed with retinal vascular occlusion not associated with vaccination (53 years old) [25].…”
Section: Discussionsupporting
confidence: 53%
“…In addition, many lipid trait SNPs carry metabolic syndrome trait effects, especially diabetes, which is an important and concerning confounder. A low HDL-C level is associated with a higher risk of type 2 diabetes ( 39 ) and studies have shown that RVO is associated with diabetes ( 40 ). After adjusting for diabetes, MVMR analysis demonstrates that low HDL-C may be an independent risk factor for RVO, suggesting that controlling of HDL-C level may be effective in managing RVO.…”
Section: Discussionmentioning
confidence: 99%
“…16 Hyperlipidemia is a known risk factor for BRVO, and previous studies have found that statin therapy is associated with a decreased risk for BRVO. 17 Thus, the lower rate of statin use among older patients than among younger patients may have contributed to the increased proportion of older patients with hyperlipidemia in this study.…”
Section: Discussionmentioning
confidence: 83%